Highly selective adsorption of curcuminoids by ceria and hydrated ceria - Ying Wang; Rong Yang; Sijie Zhu; Zhi Huang; Shuting Xie; Xu Zhang; Gang Huang; Ming Ma; Bo Chen (Food Chemistry Advances, 2023)
In order to better develop and utilize curcuminoids, a method with high selectivity and simple and rapid separation and enrichment of curcuminoids from turmeric should be established. In this study, hydrated ceria and ceria were first prepared, and then curcumin was used as a model compound to investigate the adsorption and separation performance of the obtained adsorbed materials. Finally, ceria obtained at the calcination temperature of 400 °C were selected as the best adsorbent, and the curcuminoids in turmeric were effectively separated and enriched. This method not only has mild synthetic conditions and simple methods for adsorption materials, but also has low organic solvent consumption, simple operation and good selectivity in the separation and enrichment process, which provides a good enrichment method and research basis for the further study of curcuminoids.